1995
DOI: 10.1063/1.359522
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous alloy formation by mechanical alloying and consecutive heat treatment in Fe50B50 powder mixture

Abstract: Equiatomic composition powder mixture of pure Fe and B was mechanically alloyed in a controlled atmosphere vibration mill. Amorphous alloy phase formation was established by Mijssbauer spectroscopy and by transmission electron microscopy. The variation of the average boron concentration and the homogeneity of the amorphous phase during the alloying process was followed by MSssbauer spectroscopy. At the early stage of the milling process a broad concentration distribution (from 20 to 50 at. % Bj was observed. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…In [25] it was shown that with the content of B of 20 at.% MA was realized during one stage: Fe + B → Fe + Am(Fe-B). At the same time the stage of the amorphous phase formation precedes the formation of borides with a higher amount of B [26][27][28][29][30]. The given data show considerable similarity in the type of SSRs in the Fe-C and Fe-B systems.…”
Section: Mechanical Alloying Of Fe-c and Fe-bsupporting
confidence: 52%
See 1 more Smart Citation
“…In [25] it was shown that with the content of B of 20 at.% MA was realized during one stage: Fe + B → Fe + Am(Fe-B). At the same time the stage of the amorphous phase formation precedes the formation of borides with a higher amount of B [26][27][28][29][30]. The given data show considerable similarity in the type of SSRs in the Fe-C and Fe-B systems.…”
Section: Mechanical Alloying Of Fe-c and Fe-bsupporting
confidence: 52%
“…Additional distortions during C dissolution lead to amorphization of the interfaces. MA in the Fe-B system was studied in [25][26][27][28][29][30] with the B content in the initial mixture from 20 to 60 at.%. In [25] it was shown that with the content of B of 20 at.% MA was realized during one stage: Fe + B → Fe + Am(Fe-B).…”
Section: Mechanical Alloying Of Fe-c and Fe-bmentioning
confidence: 99%
“…Since 1992 a lot of works was carried out where authors tried to obtain amorphous Fe-B alloys using mechanical alloying (MA) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Unlike metal-metal systems where an amorphous state can often be achieved by both rapid quenching and MA techniques though at the rather different concentration ranges [22][23][24][25] it proved to be more difficult to produce Fe-B amorphous alloys by MA.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1970s, amorphous alloys have been prepared in a wide range of boron concentrations, from 10 to 60 at %, by melt quenching and deposition from a gas medium (e.g., see [1,2]); physicochemical properties of the alloys and the structural and phase transformations upon a thermal treatment have been investigated. It is not surprising that, from the 1990s until now, the structure, phase composition, and thermal stability of Fe-B samples prepared by mechanical alloying (MA) have been studied [3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%